T.JUMAMURATOVTÍŃ POEZIYASÍNDA WATAN ANA TOPÍRAQ TEMASÍNÍŃ SÚWRETLENIWI - Otarbaeva, F. (SCIENCE and SOCIETY, 2019)
In the article the author tries to show how famous Karakalpak poet T.Jumamuratov expresses his feelings – love for Motherland, his country and people in his works. The creative work of the poet takes an hanorary place in Karakalpak poetry. In the lines of his poems we can see the poet’s devotion and love for his Motherland.